2018
DOI: 10.30827/digibug.54045
|View full text |Cite
|
Sign up to set email alerts
|

Cross-Cultural Sensitivity and Intensity of Interaction in Study Abroad: A Developmental Approach

Abstract: The present study examines second language (L2) learners' development of cross-cultural sensitivity (CCS) during study abroad (SA) programs, and how intensity of interaction with L2 speakers influences the reported gains. A group of US college students participating in a SA program in Mexico completed the Inventory of Cross-Cultural Sensitivity (ICCS) questionnaire (Cushner, 1986), a language contact questionnaire, and 10 weekly journal entries. The results revealed that learners did not significantly develop … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…The research instrument used in this study to collect data was an interview reflecting IISMA 2022 awardees´ cross-cultural sensitivity and ability to effectively engage with individuals from different cultural backgrounds. The interview questions were based on Cross-Cultural Sensitivity (ICCS) indicators, developed by (Cushner, 1986;Sánchez Hernández & Alonso-Marks, 2018). The interview was conducted in written form using the chat platforms; WhatsApp and Line, and through an online interview using Zoom, depending on the participants´ preferences.…”
Section: Methodsmentioning
confidence: 99%
“…The research instrument used in this study to collect data was an interview reflecting IISMA 2022 awardees´ cross-cultural sensitivity and ability to effectively engage with individuals from different cultural backgrounds. The interview questions were based on Cross-Cultural Sensitivity (ICCS) indicators, developed by (Cushner, 1986;Sánchez Hernández & Alonso-Marks, 2018). The interview was conducted in written form using the chat platforms; WhatsApp and Line, and through an online interview using Zoom, depending on the participants´ preferences.…”
Section: Methodsmentioning
confidence: 99%
“…All participants lived with local families and socialized with their conversation partners to varying degrees, as will be reported below. As research has shown, interaction and socialization with NSs, in addition to other individual and extralinguistic factors, is one of the most effective and successful conditions for the linguistic and sociocultural development of L2 and HL learners in a SA context (Dewey et al, 2014;Kinginger & Blattner, 2008;Meier & Daniels, 2013McManus, Mitchell, & Tracy-Ventura, 2014Sánchez Hernández & Alonso-Marks, 2018).…”
Section: Methods Participantsmentioning
confidence: 99%
“…In this regard, there is a paucity of research that documents IaH efforts whilst studying abroad experiences are prominently explored in the literature (Baldassar & McKenzie, 2016); based on this understanding, this research aims to redress this gap by focusing on an IaH, at the teacher's level, strategy. Along the need for HE to become more international, it is necessary to increase in students their Intercultural Competence (ICC), mostly defined as "the ability" to "think"," act", "perform" "communicate" and "interact" in a proper and effective way in different intercultural contexts and it is mainly grounded on: cultural knowledge, skills, and attitudes (Deardorff, 2006;Echcharfy,2019;Fantini, 2007;López-Rocha, 2021;Mažeikienė & Virgailaitė-Mečkauskaitė, 2007;Sánchez Hernández & Alonso-Marks, 2018;Wickline et al, 2021) with a lesser emphasis on awareness; so that they are individuals not only able to meet the demands of the globalised workforce through effective communication, but they are able to understand and embrace different world perspectives. As a result of globalisation with individuals interconnected with much more ease, hence, experiencing more intercultural encounters; intercultural competence has become of utmost importance.…”
Section: Introductionmentioning
confidence: 99%